2017
DOI: 10.3390/su9112071
|View full text |Cite
|
Sign up to set email alerts
|

On Production and Green Transportation Coordination in a Sustainable Global Supply Chain

Abstract: This paper addresses a coordination problem of production and green transportation and the effects of production and transportation coordination on supply chain sustainability in a global supply chain environment with the consideration of important realistic characteristics, including parallel machines, different order processing complexities, fixed delivery departure times, green transportation and multiple transportation modes. We formulate the measurements for carbon emissions of different transportation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Management of the total cost in the supply chain must consider aspects such as transport costs, penalties for delays, costs for emissions, etc. Many of these costs not only have an impact on the profit and loss account, but also affect the sustainability of the supply process [6,7]. In fact, to facilitate processes within supply chains, reducing associated delays and improving the sustainability of supply chain operations, many distribution companies began to apply new systems and new techniques, as the dual-channel supply chains in which the manufacturer uses both vertical integration online and an offline intermediary [7], or the cross-docking technique that provides the fast flow of products from inbound trucks to assigned outbound trucks [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Management of the total cost in the supply chain must consider aspects such as transport costs, penalties for delays, costs for emissions, etc. Many of these costs not only have an impact on the profit and loss account, but also affect the sustainability of the supply process [6,7]. In fact, to facilitate processes within supply chains, reducing associated delays and improving the sustainability of supply chain operations, many distribution companies began to apply new systems and new techniques, as the dual-channel supply chains in which the manufacturer uses both vertical integration online and an offline intermediary [7], or the cross-docking technique that provides the fast flow of products from inbound trucks to assigned outbound trucks [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Demartini et al [48] analyzed the sustainability in soft drink supply chains to determine the sustainable best practices and the key performance indicators that are the most related to the sustainability issues. Guo et al [49] proposed a hybrid genetic algorithm approach to examine how the supply chain sustainability can be affected by the coordination between the production and transportation by considering several features such as departure times and transportation modes. The results showed that the coordination between the production and green transportation has an important impact on the global supply chain sustainability.…”
Section: Sustainability In Supply Chains and Cross-docksmentioning
confidence: 99%
“…European electricity companies, particularly distribution system operators (DSOs), are investing in the necessary infrastructure to build a single European market for EVs. European standards are indispensable to safeguard that drivers enjoy convenient EU-wide charging solutions that avoid a multiplicity of cables and adaptors and thus retrofit costs [15,16]. Today, the only standards available at European level, dealing with the charging system, plugs, and sockets, are contained in the IEC 61851 [17,18].…”
Section: Charging Modes For Evs Charging Stationsmentioning
confidence: 99%